2022
DOI: 10.1021/acs.energyfuels.2c00309
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Capillary Imbibition of Shale Oil in Nanochannels

Abstract: Shale oil has been receiving more and more attention, because of its promising contribution to energy development and utilization. Capillary imbibition in shale nanopores widely exists in the storage and recovery of shale oil. Despite the ubiquitous nature, shale oil imbibition in nanoconfined space and the effect of nanopore walls on flow are still unclear. Here, we report an experimental study of shale oil capillary imbibition in single nanochannels with heights ranging from 34 nm to 100 nm. Nanofluidic chip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…(1) Theoretically, the fluid phase behavior in shale matrix needs further study. There are lack of full understanding about the main controlling factors for the change of critical parameters of alkanes, accuracy of capillary force estimation and reliability of phase state prediction, and the adsorption characteristics of alkanes (Zhang et al, 2017;Wang X. et al, 2018;Wu et al, 2019;Lu et al, 2022). As to fluid flow mechanisms through shale multiscale pore networks, it is necessary to develop better mathematical models for characterizing transport properties, because most prior research primarily concentrated on the transport processes of single-phase flow and few studied the behavior of multiphase flow.…”
Section: Challenges Of Productivity Forcast and Future Developmentmentioning
confidence: 99%
“…(1) Theoretically, the fluid phase behavior in shale matrix needs further study. There are lack of full understanding about the main controlling factors for the change of critical parameters of alkanes, accuracy of capillary force estimation and reliability of phase state prediction, and the adsorption characteristics of alkanes (Zhang et al, 2017;Wang X. et al, 2018;Wu et al, 2019;Lu et al, 2022). As to fluid flow mechanisms through shale multiscale pore networks, it is necessary to develop better mathematical models for characterizing transport properties, because most prior research primarily concentrated on the transport processes of single-phase flow and few studied the behavior of multiphase flow.…”
Section: Challenges Of Productivity Forcast and Future Developmentmentioning
confidence: 99%
“…In the past, pressure-driven flows of liquid hydrocarbons in nanochannels have been extensively investigated by molecular dynamics (MD) simulations, which are a widely used tool to study fluid transport at the atomic scale. When confined in nanochannels with a width of several molecular layers, oil molecules exhibit unique structures, and intramolecular interactions change dramatically due to the strong interactions between the molecules and the confining channel walls. As such, the flow behavior of oil can be changed by adjusting the wall–liquid interactions. For instance, tuning the surface chemistry of channel walls can greatly affect the wall–liquid interactions and thus alter the transport in the channel. Moreover, introducing a second phase (e.g., water) has also been proven to efficiently enhance the oil transport rate because of the reduced interactions between oil molecules and the surfaces. Among the reported theoretical research on oil transport in nanochannels, oil molecules were observed to flow with negligible velocity fluctuations under a constant driving force or uniform pressure gradient under a steady state.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, polymer microspheres are usually micrometer-sized and not suitable for low-permeability and tight reservoirs . Due to the complexity of the low-permeability and tight reservoir pore structure and strong heterogeneity, the flow and plugging mechanism of microspheres are different from those of a conventional reservoir, which needs further investigation. …”
Section: Introductionmentioning
confidence: 99%